1996
DOI: 10.1093/humrep/11.2.345
|View full text |Cite
|
Sign up to set email alerts
|

The sperm centriole: its inheritance, replication and perpetuation in early human embryos

Abstract: The inheritance, replication and perpetuation of the sperm centriole in the early human embryo are reported. Both normal monospermic and abnormal dispermic embryos (n = 127) were examined by transmission electron microscopy. Centrioles were traced from fertilization to the hatching blastocyst stage. The sperm proximal centriole is introduced into the oocyte at fertilization and remains attached to the expanding spermhead during sperm nuclear decondensation, as it forms the male pronucleus. A sperm aster is ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
128
1
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(134 citation statements)
references
References 0 publications
4
128
1
1
Order By: Relevance
“…Transmission electron microscopy (TEM) analysis revealed that centrosomes are duplicated at the PN stage, when male and female PNs are in close association [12,13]. Human oocytes lack centriolar structures [12] whereas human sperm have centrioles, and as a result, the zygotic centrosome must be derived from the sperm in human zygotes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transmission electron microscopy (TEM) analysis revealed that centrosomes are duplicated at the PN stage, when male and female PNs are in close association [12,13]. Human oocytes lack centriolar structures [12] whereas human sperm have centrioles, and as a result, the zygotic centrosome must be derived from the sperm in human zygotes.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the centriole is transported by sperm into oocytes and the sperm centrosome forms a sperm aster after the centriole duplicates at the PN stage [12,13]. Therefore, the number of centrosomes represents the number of sperm that have entered into oocyte because human oocytes lack centriolar structures [12].…”
Section: Introductionmentioning
confidence: 99%
“…Most likely due to the difficulties to gather both centrioles of one centrosome or even both centrosomes at the same section plane in the voluminous ooplasm, double centrioles are not found at each pole of the first cleavage spindle. But afterwards, centrioles are then found at every stage of early embryo development (Sathananthan et al, 1996;Sathananthan, 1997). In bovine, centrioles are likewise paternally inherited, and organize the sperm aster after fertilization .…”
Section: Centrosomes In Germ Cellsmentioning
confidence: 99%
“…In bovine, centrioles are likewise paternally inherited, and organize the sperm aster after fertilization . Zygotes from humans, sheep and cows thus display centrioles at the spindle poles at first mitosis, although extensive electron microscopic studies have failed to find duplex centrioles in all spindle poles during the first cleavage of human zygotes (Sathananthan et al, 1991;Sathananthan et al, 1996;Santhananthan et al, 1997;Le Guen and Crozet, 1989). In sheep zygotes, the first cleavage spindle possesses two centrioles at one pole and only one centriole at the other pole, probably owing to difficulties to gather all centrioles at the same section plane (Crozet et al, 2000).…”
Section: Centrosomes In Germ Cellsmentioning
confidence: 99%
“…Using conventional and confocal epifluorescence microscopy of fixed oocytes and embryos, it has been well established that fertilization of rhesus oocytes requires a paternally derived centrosome (Sutovsky et al 1996, Wu et al 1996. The sperm centrosome is introduced into the oocyte during sperm incorporation where it is transformed into a zygotic centrosome, capable of nucleating microtubules (Simerly et al 1995, Sathananthan et al 1996. The microtubule-based 'sperm aster' is a radially arrayed three-dimensional structure that is found adjacent to and affixed to the sperm nucleus.…”
Section: Cytoskeletal Architecture During Primate Ivfmentioning
confidence: 99%